Research protocol for impact assessment of a project to scale up food policies in the Pacific - Dori Patay; Kathy Trieu; Briar McKenzie; Shanthi Ramanathan; Alexis Hure; Colin Bell; Anne-Marie Thow; Steven Allender; Erica Reeve; Aliyah Palu; Mark Woodward; Gade Waqa; et al. (Health Research Policy and Systems, 2022)
Abstract Background One of the challenges for countries implementing food policy measures has been the difficulty in demonstrating impact and retaining stakeholder support. Consequently, research funded to help countries overcome these challenges should assess impact and translation into practice, particularly in low-resource settings. However, there are still few attempts to prospectively, and comprehensively, assess research impact. This protocol describes a study co-created with project implementers, collaborative investigators and key stakeholders to optimize and monitor the impact of a research project on scaling up food policies in Fiji. Methods To develop this protocol, our team of researchers prospectively applied the Framework to Assess the Impact from Translational health research (FAIT). Activities included (i) developing a logic model to map the pathway to impact and establish domains of benefit; (ii) identifying process and impact indicators for each of these domains; (iii) identifying relevant data for impact indicators and a cost–consequence analysis; and (iv) establishing a process for collecting quantitative and qualitative data to measure progress. Impact assessment data will be collected between September 2022 and December 2024, through reports, routine monitoring activities, group discussions and semi-structured interviews with key implementers and stakeholders. The prospective application of the protocol, and interim and final research impact assessments of each project stream and the project as a whole, will optimize and enable robust measurement of research impact. Discussion By applying this protocol, we aim to increase understanding of pathways to impact and processes that need to be put in place to achieve this. This impact evaluation will inform future projects with a similar scope and will identify transferable and/or translatable lessons for other Pacific Island states and low- and middle-income countries.